Comparison of total phenolic compounds and antioxidant activity of four brands of infusions of Hibiscus sabdariffa (Malvaceae) marketed in Costa Rica - Agüero, Melissa; Segura, Cindy; Parra, Jonathan (Uniciencia, 2014)
Consumption of Roselle (Hibiscus sabdariffa) infusion is widespread in Costa Rica due to its known cardioprotective effects associated with the presence of phenolic compounds, mainly consisting of anthocyanins. This paper established the differences in the phenolic compounds profile and their corresponding antiradical activity amongst different distributors of Hibiscus sabdariffa infusion in Costa Rica. Tannins, flavonoids and anthocyanins were identified qualitatively. The total quantity of phenolic compounds was calculated using the Folin-Ciocalteu methodology and the antioxidant activity was quantified using the DPPH method. Results show all samples contained phenolic compounds, including anthocyanins. However, there are significant differences in the content of phenolic compounds and their corresponding antiradical activity amongst the different manufacturers of infusions. Therefore, we can conclude that the phenolic compound profile of infusions in this study varies according to each manufacturer.